Probing topological quantum phase transitions via photonic spin Hall effects in spin-orbit coupled 2D quantum materials. (6th December 2021) - Shah, Muzamil
Abstract: Topological photonics is an emerging field in photonics in which various topological and geometrical ideas are used to manipulate and control the behavior of light photons. The interplay between topological matter and the spin degree of freedom of photons provides new opportunities for achieving spin-based photonics applications. In this paper, the photonic spin Hall effect (PSHE) of reflected light from the surface of the topological silicene quantum systems subjected to external electric and radiation fields in the terahertz regime is theoretically investigated. By tuning the external electric and the applied laser fields, we can drive the silicenic system through different topological quantum phase transitions. We demonstrate that the in-plane and transverse spatial spin dependent shifts exhibit extreme values near Brewster's angles and away from the optical transition frequencies. We reveal that the photonic spin Hall shifts are sensitive to the spin and valley indices as well as to the number of closed gaps. We believe that the spin and valley-resolved PSHE will greatly impact the research in spinoptics, spintronics, and valleytronics.